ANALISIS KINERJA KARYAWAN BERDASARKAN BUDAYA ORGANISASI DAN MOTIVASI - Sugiharti, Sugiharti (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2017)
This study anlyzes The Factors Affecting the Organization and Motivation Cultures towards the Improvement of the Employees’ Work.The reserach variables and indicators refer to the porevious studies. A Model is developed and 4 hypothesis are formulated to answer the research problems.The reserach respondents are 102 people of SMAN Semarang’s employees. The instruments for the data analysis applied in this study is Double Regression. The data analysis shows that the result of this study is well accepted. This result proves that the Organisation Culture has positive impact on the employees’ improvement. The employees’ motivation has also positive impact on their work.